Analisis Kesulitan dalam Menyelesaikan Soal Persamaan Linear Satu Variabel dengan Metode Demonstrasi untuk Siswa Kelas VII SMP Negeri 5 Lamboya - Raja, Angelina Laja; Making, Samuel Rex Mulyadi; Lede, Yulius Keremata; Lubur, Dorothea Novia Ludo (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to find out the difficulties of students in solving PLSV problems using the demonstration method for grade VII students of SMP Negeri 5 Lamboya. This study uses a qualitative approach with a descriptive method. 14 students as subjects to be researched to the extent to which the students can work on one-variable lienar equation problems. The data collection methods used are tests, interviews, and documentation. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. The results of the study showed that there was still a lack of ability of students to solve PLSV questions that answered the questions correctly and incorrectly. The results of the analysis for problems number 1, 2 and 3 were at the stage of difficulty in interpreting mathematical language (59.66%), the stage of difficulty in using data (64.33%), the stage of difficulty in mastering concepts correctly (66.66%), the stage of difficulty in using calculation operations (66.66%), and the stage of difficulty in drawing conclusions (83.33%). The cause of incompetence is that students do not read the questions carefully so that they make mistakes in writing down what is known and what is asked, so that they are less able to solve problems, in a hurry so that others are incomplete.